A systematic literature review on BPMN extensions. Issue 6 (18th November 2019) - Zarour, Karim; Benmerzoug, Djamel; Guermouche, Nawal; Drira, Khalil
Abstract : Purpose: Business Process Model and Notation (BPMN) is a generic language that is often extended by researchers, either for dealing with processes of specific domains or for improving the language itself. The purpose of this paper is to present a literature review that aims to determine the current state of the art of BPMN extensions and identify the gaps that should be filled in this research area. Design/methodology/approach: For a comprehensive and effective analysis, a systematic literature review was conducted. After the collection and filtering of papers, 52 extensions were retained to be thoroughly examined and compared according to a set of criteria including objective, targeted domain, conformity to the extension mechanism, demonstration, implementation, etc. Findings: The representation of the results in the form of tables and graphs allowed the authors to deduce several positive points on the extensions as their demonstration through concrete examples. On the other hand, the authors have observed several shortcomings and suggested recommendations for addressing them. Originality/value: To the best of the authors' knowledge, the literature review is the only one that evaluates and compares all BPMN extensions over the last four years, based on several criteria covering different aspects. Furthermore, the authors were able to verify the conformity of extensions as they were published after the introduction of the BPMN extension mechanism by the Object Management Group.